A MARKETING BOOKLET: A WAY TO PROMOTE SWK 95 HOTEL TO ITS PROSPECTS AND CUSTOMERS - Serafine Limantoro; Jusuf I Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2015)
SWK 95 Hotel is a new budget hotel located near Petra Christian University. As a new hotel, SWK 95 is only known by a few people in certain areas. Moreover, there are two other hotels which are older and bigger than SWK 95 Hotel. Therefore, it is better for SWK 95 Hotel to start targeting companies and travel agencies. To accomplish this goal, a marketing booklet is the best solution to solve the problem of SWK 95 Hotel. There are five parts in this marketing booklet: table of contents, company overview (“About SWK 95”), products (“Room Types”), Facilities (“Facilities”), and contact information. By having these information, the marketing booklet will be able to help SWK 95 in introducing its hotel, reaching and getting more customers, increasing its income, developing its hotel, and becoming a big hotel